Dataset on effect of cadmium and lead on chemical reactivity of selected heterocyclic compounds as potential dipeptidyl peptidase III inhibitors using insilico methodMendeley Data - Kehinde Adeola Bolaji; Abel Kolawole Oyebamiji; Godwin Oladele Olutona (Data in Brief)
The role played by heterocyclic compounds in drug design and discovery remain crucial globally. In this work, the effect of cadmium and lead were investigated on the chemical reactivity of selected heterocyclic compounds with potential anti-dipeptidyl peptidase III activity using insilico method. Various software such as Spartan 14 (for optimization), molecular operating environment (moe) (for induced fit docking) and ADMETSar (pharmacokinetic examination) were used to execute the investigations. Three descriptors (highest occupied molecular orbital energy (EHOMO); lowest unoccupied molecular orbital energy (ELUMO) and energy gap) were observed among others for selected compounds without any foreign attachment, selected compounds with cadmium and selected compounds with lead. The calculated descriptors revealed that cadmium had a great effect on compound 7 in term of HOMO energy and energy gap. Also, it was observed that cadmium altered the ability of compound 5 in term LUMO energy. The selected compounds were docked against dipeptidyl peptidase III and the scoring was reported. More so, pharmacokinetic examination of ligands with highest binding affinity was reported and compared to the report for the reference molecules.